PENERAPAN AUDIT MANAJEMEN UNTUK MENGUKUR KINERJA SUMBER DAYA MANUSIA BAGIAN PEMASARAN - Aprliasari, Ria Dini (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is (1) to understand the human resources management audit implementation in assessing marketing department performance, and (2) to analyze things which improve marketing performance. Qualitative descriptive approach is used as the data analysis technique which is performed by collecting necessary data which is related to the management audit in order to measure the human resources performance at PT Tiga Berlian Mandiri Surabaya.The result of human resources management audit shows that the problem which is encountered by PT Tiga Berlian Mandiri Surabaya is the placement of employees does not match with their competency and the training procedures do not match with the goal-setting work. The existence of the placement of employees does not match with their competency, so the human resources performance is ineffective and inefficient. Apart from that, the training procedures do not match with the goal-setting work. The loss of motivation occurs because the employees are not motivated to do their best on their tasks. The employees do not know their strengths and weaknesses since the placement of employees does not matched with their competency.In accordance with the human resources of marketing department management audit, it is expected that the company management party is able to analyze and to make policies to the improvement so the human resources of marketing department management audit can be the control instrument on marketing department so effectiveness and efficiency of marketing department can be achieved since marketing is the front line of the company in marketing its products.Keywords: management audit, marketing and human resources performance